HUBUNGAN PERSONAL BRANDING PIMPINAN TERHADAP ENGAGEMENT ANGGOTA ORGANISASI BEM UNIVERSITAS TEKNOLOGI SUMBAWA - Rosandi, Fitra; Atmasari, Ayuning (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Personal Branding is a strategy for building a personal image or brand in the eyes of others. Personal branding has become an important factor in helping leaders manage their organizations, especially as it relates to the engagement of organizational members. The purpose of this study is to examine the relationship between the leader's personal branding and the engagement of members within the Student Executive Board (BEM) at UTS. This research uses a quantitative correlational method. The sampling technique used is purposive sampling, with the selection of participants based on specific criteria. The sample consists of 43 members of the UTS Student Executive Board. Data were collected using research instruments in the form of a Personal Branding Scale and an Engagement Scale. The results of the study show a positive correlation between personal branding and engagement, with a correlation coefficient value of 0.440 and a significance value of p = 0.003 (p < 0.05). The positive relationship indicates a unidirectional association, meaning that the better the leader's personal branding, the higher the level of member engagement. Conversely, poor personal branding by the leader is associated with lower member engagement Keyword : Personal Branding, Engagement, Organization